2008
DOI: 10.1021/bi801911v
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Specificity Determinants of Amino Acid Recognition by Arginase

Abstract: Arginase is a binuclear manganese metalloenzyme that serves as a therapeutic target for the treatment of asthma, erectile dysfunction, and atherosclerosis. In order to better understand the molecular basis of inhibitor affinity, we have employed site-directed mutagenesis, enzyme kinetics, and X-ray crystallography to probe the molecular recognition of the amino acid moiety (i.e., the α-amino and α-carboxylate groups) of substrate l-arginine and inhibitors in the active site of human arginase I. Specifically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…4B) (Shishova et al, 2009). These loops 1 and 2 are positioned between b4 and a5 in GbuA, and b5 and a6 in GpuA, respectively.…”
Section: Determinants Of Substrate Specificity By Gbua and Gpuamentioning
confidence: 99%
See 1 more Smart Citation
“…4B) (Shishova et al, 2009). These loops 1 and 2 are positioned between b4 and a5 in GbuA, and b5 and a6 in GpuA, respectively.…”
Section: Determinants Of Substrate Specificity By Gbua and Gpuamentioning
confidence: 99%
“…Therefore, these enzymes may have evolved from a common ancestral protein and diverged into their particular functions with different substrate specificities (Arakawa et al, 2003;Dowling et al, 2008;Itoh, 2002, 2005;Sekowska et al, 2000). Previous reports showed that substrate recognition is mainly determined by the loops around the active site, which allows diverse guanidine substrates to be accommodated for catalysis (Ahn et al, 2004;Bewley et al, 1999;Cama et al, 2003;Di Costanzo et al, 2005Elkins et al, 2002;Kanyo et al, 1996;Shishova et al, 2009). Crystal structures of ureohydrolases are available for rat liver arginase I (Kanyo et al, 1996), human arginase I (Di Costanzo et al, 2005), human arginase II (Cama et al, 2003), Bacillus caldovelox arginase (Bewley et al, 1999), Streptomyces clavuligerus PAH (Elkins et al, 2002), and Deinococcus radiodurans agmatinase (Ahn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Manganese (Mn) is an essential nutrient important to protein and energy metabolism, bone mineralization, metabolic regulation, and cellular protection from reactive oxygen species. It is a cofactor for enzymes, such as mitochondrial superoxide dismutase (Hearn et al 2003), arginase (Shishova et al 2009), pyruvate carboxylase (Zwingmann et al 2004), and glutamine synthetase (Takeda 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The first X-ray structure of arginase I was of the rat liver enzyme and revealed the bi-atomic manganese centre which is the hallmark of this enzyme (Kanyo et al, 1996). Previous work has provided high-resolution crystal structures of hArginase I with the tight-binding substrate analogues 6-boronohexanoic acid (ABH) and S-(2-boronoethyl)-l-cysteine (BEC), along with various other molecules (Shishova et al, 2009;Ilies et al, 2010;Di Costanzo et al, 2005Baggio et al, 1997). There has also been a report of an unliganded hArginase I structure (PDB code 2pha): in this instance, the protein was crystallized in the presence of a small molecule which was not seen in the subsequent structure (Di Costanzo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%